Vdrive Evaluation of Remote Steering and Testing in Lasso Electrophysiology Procedures Study: The VERSATILE Study in Atrial Fibrillation Ablation. (March 2016) - NÖLKER, GEORG; SCHWAGTEN, BRUNO; DEVILLE, J. BRIAN; BURKHARDT, J. DAVID; HORTON, RODNEY P.; SHA, QUN; TOMASSONI, GERY
Remote Navigation of Circular Mapping Catheters: Introduction: Circular mapping catheters (CMC) are an essential tool in most atrial fibrillation ablation procedures. The Vdrive™ with V‐Loop™ system enables a physician to remotely manipulate a CMC during electrophysiology studies. Our aim was to compare the clinical performance of the system to conventional CMC navigation according to efficiency and safety endpoints. Methods and Results: A total of 120 patients scheduled to undergo a CMC study followed by pulmonary vein isolation (PVI) were included. Treatment allocation was randomized 2:1, remote navigation:manual navigation. The primary effectiveness endpoint was assessed based on both successful navigation to the targeted pulmonary vein (PV) and successful recording of PV electrograms. All PVs were treated independently within and between patients. The primary safety endpoint was assessed based on the occurrence of major adverse events (MAEs) through seven days after the study procedure. Primary effectiveness endpoints were achieved in 295/302 PVs in the Vdrive arm (97.7%) and 167/167 PVs in the manual arm (100%). Effectiveness analysis indicates Vdrive non‐inferiority (pnon‐inferiority = 0.0405; δ = –0.05) per the Cochran–Mantel–Haenszel test adjusted for PV correlation. Five MAEs related to the ablation procedure occurred (three in the Vdrive arm—3.9%; two in the manual arm—2.33%). No device‐related MAEs were observed; safety analysis indicates Vdrive non‐inferiority (pnon‐inferiority = 0.0441; δ = 0.07) per the normal Z test. Conclusion: Remote navigation of a CMC is equivalent to manual in PVI in terms of safety and effectiveness. This allows for single‐operator procedures in conjunction with a magnetically guided ablation catheter.